Manual neuronavigation for superior semicircular canal dehiscence surgery - Altamami, Nasser; Khoury, Michel; Saliba, Issam (Frontiers in Neurology, 2023)
Background Intraoperative identification of a superior semicircular canal (SSC) dehiscence via the middle cranial fossa approach (MCFA) remains a difficult endeavor without a neuronavigation system. To address these challenges, we propose a technique to localize the SSC dehiscence intraoperatively using certain anatomical landmarks. Method Three anatomical landmarks should be identified on preoperative radiological images: the distance from the squamous part of the temporal bone to the dehiscent SSC, the lower limit of the craniotomy, and the exact location of the craniotomy in relation to the bony external auditory canal. The use of these landmarks intraoperatively can allow the surgeon to correctly identify the position of the SSC. Two instructional videos explaining this technique are presented. Conclusion The proposed manual neuronavigation technique seems to be an accurate, safe, and cost-effective alternative technique for use in SSC dehiscence surgery.